Gill Monogeneans of Potentially Cultured Tilapias and First Record of Cichlidogyrus mbirizei Bukinga et al., 2012, in Thailand - LERSSUTTHICHAWAL, Theerawoot; MANEEPITAKSANTI, Worawit; PURIVIROJKUL, Watchariya (Walailak Journal of Science and Technology (WJST), 2015)
Monogeneans are pathogenic flatworms commonly found in many fish species. To avoid the risk of economic loss, parasitological investigation is necessary. A survey of gill monogeneans from 45 red hybrid tilapias (Oreochromis sp.) in Kanchanaburi province, Thailand, was conducted. Fish samples were infested with 6 gill monogenean species, viz., Cichlidogyrus sclerosus, C. thurstonae, C. halli, C. mbirizei, C. tilapiae, and Scutogyrus longicornis. Morphologically, unidentified Cichlidogyrus species from cultured red tilapia (Oreochromis niloticus ´ O. mossambicus) in Nakhon Si Thammarat province, southern Thailand, collected in 2012 and C. mbirizei, found in this study, were similar. This finding provides new host and locality records for C. mbirizei as a new pathogenic gill monogenean in Thailand. According to the original type host (Oreochromis tanganicae) and habitat of C. mbirizei, it was strongly suggested that C. mbirizei can be translocated with the host during fish trading. For practical identification, a key of gill monogeneans on tilapia in Thailand is also provided herein.